Enhanced production of interleukin 1-beta by mononuclear cells isolated from mucosa with active ulcerative colitis of Crohn's disease. - Mahida, Y; Wu, K; Jewell, D (1989)
IL1-beta production by mononuclear cells isolated from normal and active inflammatory bowel disease mucosa was studied. Significantly more IL1-beta was produced spontaneously by mononuclear cells from the inflamed mucosa compared with those from normal colonic mucosa (median 190 pg/ml (range 45-700) v 20 pg/ml (0-165)). Stimulation with lipopolysaccharide enhanced IL1-beta production by mononuclear cells from active inflammatory bowel disease mucosa but not those from normal mucosa. Depleting the mononuclear cells of macrophages, by panning with monoclonal antibody 3C10, reduced the amount of IL1-beta produced. Enhanced IL1-beta production from the inflamed mucosa may play an important role in the mediation of many inflammatory responses. The enhanced production appears to be the result of a recruited population of cells.